Assessing upper extremity-cognitive dual-task ability in neurological populations: A systematic review. - Bachar Kirshenboim, Yishai; Weitzer, Tal; Rand, Debbie (NeuroRehabilitation, 2023)
BACKGROUND: Dual-task involves performing cognitive and motor tasks together, which requires executive functions that may be impaired in individuals with neurological conditions. Therefore, it is important to accurately assess executive functions to plan a therapeutic intervention. OBJECTIVE: To characterize the use of upper extremity-cognitive dual-task assessment and to describe variables correlated with dual-task ability. METHODS: An electronic search of databases (MEDLINE, EMBASE, CINAHL, and PsycINFO) was carried out using a combination of the following terms: upper-extremity, dual/concurrent task, and cognitive/motor tasks. Two reviewers independently completed data extraction and assessed study quality. RESULTS: 1,946 studies were identified; 25 studies met the inclusion criteria. The purpose of using an upper extremity-cognitive dual-task assessment varied between studies as well as the upper extremity motor tasks used: pegboard (N = 14), arm curl (N = 9), finger-tapping (N = 3), and reaching (N = 1) tests. Dual-task ability was reported as the motor-cognitive interference (N = 15) and as motor cost (N = 12). Dual-task ability was correlated to cognition, brain activity, and daily function, and was significantly different between healthy and neurological individuals. CONCLUSION: Upper extremity cognitive dual-task paradigm is gaining popularity in clinical research, but lacks standardized tools, testing procedures, and calculations. A structured assessment procedure is needed for clinical use and future research.